The influence of predecessors on the elements of the structure of productivity and quality of winter wheat grains depending on high quality characteristics - Жемела, Г. П.; Курочка, А. О. (Scientific Progress & Innovations, 2012)
The influence of the predecessors on the elements of the structure of productivity: the amount of productive stems per 1 m, the amount of grains in the ear of wheat, the mass of 1000 grains, the nature, the glassiness of different sorts of soft winter-annual wheat according to the biological characteristics was examined. It was found out that the best predecessors were pears and annual bean herds. The sorts Zemlyachka, Volodarka, Dobirna had the best physical indicators of grain quality.